C‐/Ka‐band circularly polarized shared‐aperture antenna array. Issue 11 (14th September 2022) - Yang, Yong; Ban, Yong‐Ling; Sun, Qiang; Sim, Chow‐Yen‐Desmond
Abstract: A C‐/Ka‐band circularly polarized (CP) shared‐aperture scanning antenna array has been proposed in this paper. Here, the antenna array working in the C‐band (6.48–6.52 GHz) is composed of 4 × 4 cross‐dipole antenna elements, and each cross‐dipole antenna element is fed by a 1‐to‐2 power divider with 90° phase difference, so that it can induce left/right‐hand CP wave. As for the antenna array working in the Ka‐band (27.5–28.5 GHz), it is made up of 16 × 16 CP antenna elements, in which each CP antenna element is an aperture‐coupled chamfered patch fed by substrate integrated waveguide (SIW) structure. To realize the proposed scanning array, the C‐band antenna array is set within the gap between adjacent antenna elements of the Ka‐band antenna array, and the radiation apertures of all the antenna elements are printed on the same plane. Notably, such a layout can yield good isolation performance between the C‐band antenna and the Ka‐band antenna element. From the measured results, in the C‐band, the proposed scanning array can achieve a beam scanning range of 0°–38° with axial ratio (AR) < 3 dB, a port isolation of greater than 45 dB, and a maximum gain of 18.2 dBic. On the other hand, in the Ka‐band, the proposed scanning array can yield a beam scanning range of 0°–45° with AR <3 dB, a port isolation of greater than 37 dB, and a maximum gain of 26.2 dB.